2013
DOI: 10.1177/1745691613497965
|View full text |Cite
|
Sign up to set email alerts
|

Minority Stress and Physical Health Among Sexual Minorities

Abstract: Lesbian, gay, and bisexual (LGB) individuals suffer serious mental health disparities relative to their heterosexual peers, and researchers have linked these disparities to difficult social experiences (e.g., antigay victimization) and internalized biases (e.g., internalized homophobia) that arouse stress. A recent and growing body of evidence suggests that LGB individuals also suffer physical health disparities relative to heterosexuals, ranging from poor general health status to increased risk for cancer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
467
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 645 publications
(487 citation statements)
references
References 187 publications
(296 reference statements)
12
467
1
7
Order By: Relevance
“…King et al (2008), for example, report results from a metaanalysis of previous studies showing that the risks of depression and anxiety disorders, and of alcohol and substance dependence, are at least 1.5 times higher within LBG populations, and suicide attempts around twice as likely, than in heterosexual populations. Subsequent research mostly confirms this finding of marked difference in mental health disorders (e.g., Cochran and Mays, 2009;Bolton and Sareen, 2011;Chakraborty et al 2011 Research Council, 2011;Lick et al, 2013).…”
Section: Healthmentioning
confidence: 77%
“…King et al (2008), for example, report results from a metaanalysis of previous studies showing that the risks of depression and anxiety disorders, and of alcohol and substance dependence, are at least 1.5 times higher within LBG populations, and suicide attempts around twice as likely, than in heterosexual populations. Subsequent research mostly confirms this finding of marked difference in mental health disorders (e.g., Cochran and Mays, 2009;Bolton and Sareen, 2011;Chakraborty et al 2011 Research Council, 2011;Lick et al, 2013).…”
Section: Healthmentioning
confidence: 77%
“…Examining the effect of sexual minority stress at the individual level is important as it has been shown to contribute to deleterious mental and physical health outcomes (e.g., Frost, Lehavot, & Meyer, 2013;Lick, Durso, & Johnson, 2013), as well as to lower relationship quality (e.g., Frost & Meyer, 2009). Notably, the conceptualization of sexual minority stress has recently been expanded to account for the way this process may operate at the couple level.…”
Section: Sexual Minority Stressmentioning
confidence: 99%
“…In addition to possible challenges related to intimate relationships, the inclusion of children, employment and financial stress can contribute to an increase in personal struggles. [40][41][42]. Relationships can also be violent.…”
Section: Perils Of Legalizing Marriagementioning
confidence: 99%
“…Same-sex partnerships have the same stressors as opposite-sex couples and often anxieties are intensified due to LGBTQ discrimination. Some studies have found that "minority stress" and prejudice that LGBTQ individuals face have a deleterious effect on their health and relationships [41,42,[44][45][46][47][48][49][50][51]. The marketing campaign in favor of same-sex marriage rights depicted couples as happy, secure, loving, and carefree.…”
Section: Perils Of Legalizing Marriagementioning
confidence: 99%